Supramolecular Organization of Nonstoichiometric Drug Hydrates: Dapsone - Braun, Doris E.; Griesser, Ulrich J. (Frontiers in Chemistry, 2018)
The observed moisture- and temperature dependent transformations of the dapsone (4,4′-diaminodiphenyl sulfone, DDS) 0.33-hydrate were correlated to its structure and the number and strength of the water-DDS intermolecular interactions. A combination of characterization techniques was used, including thermal analysis (hot-stage microscopy, differential scanning calorimetry and thermogravimetric analysis), gravimetric moisture sorption/desorption studies and variable humidity powder X-ray diffraction, along with computational modeling (crystal structure prediction and pair-wise intermolecular energy calculations). Depending on the relative humidity the hydrate contains between 0 and 0.33 molecules of water per molecule DDS. The crystal structure is retained upon dehydration indicating that DDS hydrate shows a non-stoichiometric (de)hydration behavior. Unexpectedly, the water molecules are not located in structural channels but at isolated-sites of the host framework, which is counterintuitively for a hydrate with non-stoichiometric behavior. The water-DDS interactions were estimated to be weaker than water-host interactions that are commonly observed in stoichiometric hydrates and the lattice energies of the isomorphic dehydration product (hydrate structure without water molecules) and a stable anhydrate at room temperature (form III) differ only by approximately 1 kJ mol–1. The computational generation of hypothetical monohydrates confirms that the hydrate with the unusual DDS:water ratio of 3:1 is more stable than a feasible monohydrate structure. Overall, this study addresses the critical class of non-stoichiometric hydrates, highlighting that only a multidisciplinary investigation can unravel hydrate formation at a molecular level, knowledge which is a requirement in modern drug development.